Reproductive performance of murrah buffaloes - SAINI, M S; PANDER, B L; YADAV, R S; GREWAL, S S; SINGH, N (The Indian Journal of Animal Reproduction, 2023)
Data on 744 Murah buffaloes maintained at Buffalo Research Centre, CCS Haryana AgriculturalUniversity, Hisar from the year 1993-94 to 2000-2001 were analysed for studying the trends inreproductive traits. A significant decrease in age at first calving (AFC) was observed over the years,the age decreased from 1570 (during 1993-94) to 1440 days (during 1999-2000). No definite patternwas observed in case of service period (SP) over the years, however, it ranged from 107 to 163 days.A similar trend was observed in calving interval (Cl), it ranged from 409 to 479 days. Calving intervaland service period improved in favourable direction with advancement of parity.
Keywords: Trends; Reproductive traits; Buffaloes